(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Measures implemented in the health care system in the Uzbek SSR in 1914-1974 and the state of medical and clinical care intended for the provision of emergency medical care and emergency medical care to the population by the employees of the sanitary-epidemiological control and station and identifying key indicators.